Clarifying the Link Between Amygdala Functioning During Emotion Processing and Antisocial Behaviors Versus Callous-Unemotional Traits Within a Population-Based Community Sample. (September 2020) - Dotterer, Hailey L.; Waller, Rebecca; Hein, Tyler C.; Pardon, Alicia; Mitchell, Colter; Lopez-Duran, Nestor; Monk, Christopher S.; Hyde, Luke W.
Prominent theories suggest that disruptions in amygdala reactivity and connectivity when processing emotional cues are key to the etiology of youth antisocial behavior (AB) and that these associations may be dependent on co-occurring levels of callous-unemotional (CU) traits. We examined the associations among AB, CU traits, and amygdala reactivity and functional connectivity while viewing emotional faces (fearful, angry, sad, happy) in 165 adolescents (46% male; 73.3% African American) from a representative, predominantly low-income community sample. AB was associated with increased amygdala activation in response to all emotions and was associated with greater amygdala reactivity to emotion only at low levels of CU traits. AB and CU traits were also associated with distinct patterns of amygdala connectivity. These findings demonstrate that AB-related deficits in amygdala functioning may extend across all emotions and highlight the need for further research on amygdala connectivity during emotion processing in relation to AB and CU traits within community populations.